Safeguarding the future: Forecasting cybersecurity and privacy challenges and solutions in emerging technologies for SMEs - Campos, D. M.; Coutinho, C. (Procedia Computer Science, 2025)
Small and medium-sized enterprises (SMEs) are increasingly vulnerable to cybersecurity threats, risking their operations and growth. This paper examines SMEs' specific weaknesses and identifies effective protection strategies. Combining quantitative tests and qualitative surveys and interviews, the study highlights key challenges like limited resources, lack of expertise, and emerging technology threats. It investigates the impact of quantum computing, which could compromise current encryption methods, and Artificial Intelligence (AI), which can enhance threat detection. The findings guide SMEs in adopting new technologies, improving employee training, and bolstering cybersecurity. The paper aims to develop tailored cybersecurity plans to ensure SMEs' safety and success in the digital age.